Effect of soil degradation on leaf decomposition and nutrient release under humid tropical conditions - Tian, G. (1998)
Characterization of degradation of an Alfisol caused by clearing and long-term cultivation and the effect of the degradation on leaf (Cajanus cajan) decomposition and nutrient (N and P) release were studied in the humid zone of southwest Nigeria. Degradation of the Alfisol as a result of land clearing and 17-year continuous cropping led to loss of soil biota and deterioration of soil physical and chemical properties. Compared with nondegraded soil, the degraded soil was 38% lower in soil organic carbon, 55% lower in exchangeable bases, 56% lower in microbial biomass, and had 44% lower microarthropod density, 34% less silt, and 88% less water infiltration; it also had 13% higher bulk density and 14% more sand. Soil pH was lower in the degraded than in the nondegraded soil. The macrofauna community in the degraded soil was termite-dominant (Ancistratermes cavithorax), whereas it was earthworm-dominant (Hyperiodrilus africanus) in the nondegraded soil. Leaf decomposition and nutrient release were lower in the degraded soil than in the nondegraded soil during the 150-day experiment. Higher decreases in leaf decomposition and nutrient release in the degraded soil were observed when macrofauna were excluded. Macrofauna-mediated leaf decomposition and nutrient release in the degraded soil were higher than in the nondegraded soil. Irrespective of soil degradation, macrofauna-mediated decomposition and nutrient release resulted in net nutrient mineralization.